Sahana Pradhan in the Politics of Nepal - Sapkota, Dhakaram (Tribhuvan University Journal, 2018)
Sahana Pradhan is the top most female leader in the politics of Nepal. She had to struggle a lot to stand at the level. As there was the autocratic Rana regime for more than a century, political awareness could not be developed in general public. At that time it was the great challenge for a woman to be involved in politics. Besides this, Sahana Pradhan had established her own identity by participating actively in student politics against the movement of Rana regime. She remained busy in family affairs rather than politics when she got marriage with founding general secretary of NCP, Pushpalal in 2009BS. Likewise, she joined the Tribhuvan University as the lecturer which was her obligation rather than the interest. But that obligation also got stopped due to politics. After the death of Pushpalal, she started to hold the leadership of the party and got success to be the president of Leftist Union in 2046BS. CPN (UML) which was formed by the integration of CPN (ML) and CPN (Marxism) in 2047BS, got the opportunity to lead the government as the largest party of the country in midterm election of 2051BS. After the split of CPN (UML) all the political enthusiasm got stopped. However, the name Sahana Pradhan got introduced in the history of Nepali Politics.